Issues of organization of nutrition in kindergartens and schools in the Republic of Kazakhstan. Comparative Assessment - Issabayeva Moldir (European Research Materials, 2024)
The aim of the research was to make a comparative assessment of the actual nutrition of preschool children in consideration of changes in sanitary legislation regarding the organization of public nutrition. Materials and Methods: Nutrition was assessed based on the study of two-week implemented menus in 4 preschool organizations. The analysis of the nutritional and biological value of children’s diets was carried out according to the main indicators of regulatory documents and legislative acts. A comparative characteristic of the actual food set was conducted, taking into account the changes in the newly enacted sanitary and epidemiological SanPiN rules and norms. Our research aims to explore these troubling health trends among school children in Kazakhstan and examine how they are linked to the organization of nutrition in educational settings. This study will offer a comprehensive analysis that could potentially influence policy changes in this crucial sector. The structure of the food set provided to children in preschool organizations was found to be irrational. Optimal consumption (from 94 to 104% of the norm) of basic food products (meat, poultry, milk and dairy products, cottage cheese, sour cream, eggs) was determined. The analyzed menus had deficiencies in rye bread, fish, fruits, and an excess of pasta, sugar, confectionery products, and the presence of products excluded from the new food set (sausage products). The nutritional and energy value of children’s diets was sufficient compared to the norms of physiological needs; however, there was an imbalance in the intake of both macro and micronutrients, especially calcium, phosphorus, and magnesium.